Variability in grain, flour, functional properties and protein profiling in newly developed wheat genotypes grown in temperate climate of Western Himalayas - Taha Mukhtar; Abida Jabeen; Syed Zameer Hussain; Raashid Ahmad Siddiqi; Shabir H. Wani; Anju Mahendru-Singh; Tawheed Amin; Quraazah A. Amin; Mohmad Sayeed Bhat (Frontiers in Nutrition)
BackgroundSince wheat varieties and breeding lines developed by plant breeders in the western Himalayan region (Kashmir) have received limited attention with respect to their physical and protein quality characterization, the focus of the study is to evaluate the diversity in grain, flour and the various protein fractions in newly released wheat genotypes grown in temperate regions of the Western Himalayas.MethodsThe present study investigated the grain and flour quality in various newly developed advanced wheat genotypes, viz., KWQ-21-1, KWQ-21-2, KWQ-21-3, KWQ-21-4, SKW 374, KWQ-21-6, KWQ-21-7, and SKW 357, along with two released varieties (Shalimar Wheat-2 and Shalimar Wheat-3). These wheat genotypes were studied for their functional, structural and protein profiling characteristics as per the approved AACC and AOAC standard methods of analysis.ResultsThe various physical parameters varied significantly (p ≤ 0.05) between wheat genotypes. Protein content varied significantly from 8.06 to 11.39%. All the studied genotypes/varieties showed significant variations (p ≤ 0.05) with respect to proximate composition, gluten content, SDS sedimentation value, falling number and solvent capacities. Dry and wet gluten content varied from 8.78 to 13.2% and 23.27 to 33.87%, respectively. Wheat genotypes exhibited moderate SDS-sedimentation values and solvent retention values, indicating that the genotypes have moderate gluten strength and may be more suited for chapatti or biscuit making. A high degree of polymorphism in the intensity and number of bands in the molecular range of 30.7–48 kDa corresponding to the low molecular weight glutenin subunit (LMW-GS) /α-, β- and γ-gliadin region was observed in the wheat genotypes. High molecular weight (HMW) proteins varied from 76.5 to 111.5 kDa. Correlation results showed that the flour characteristics were related to each other, which can ultimately affect the end product utilization of these wheat genotypes.